The Meaning and Function of Hata-Hata in the Mangupa–Upa Procession of the Mandailing Community in Sei Deras Hulu Village, Rokan Hulu Regency - Rani Rani; Muslim Muslim (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The mangupa-upa tradition is one form of oral tradition that is still preserved and practiced in the life of the Mandailing community, especially in Sei Deras Hulu Village, Rokan Hulu Regency. This tradition does not only function as a customary procession but also contains cultural values that are transmitted through spoken expressions known as hata-hata. This study aims to examine the meanings and functions of hata-hata in the mangupa-upa oral tradition. The research employs a qualitative method with a descriptive approach. The data consist of hata-hata expressions used in the mangupa-upa procession, which are analyzed based on categories of spiritual, social, and moral meanings, as well as ritual, social, and educational functions. The results show that hata-hata in the mangupa-upa tradition contain spiritual meanings related to safety and the balance of the soul (tondi), social meanings emphasizing harmony and kinship relations, and moral meanings that teach maturity and strength of character. In addition, hata-hata function as a ritual medium, a means of reinforcing social order, and a tool for cultural education. In conclusion, the mangupa-upa tradition not only serves as an oral tradition but also as a cultural practice that plays an important role in maintaining the spiritual, social, and moral balance of the Mandailing community.